Teknologi Blockchain dalam Sistem Crowdfunding Berbasis Donasi - Alixa Arivya Tofer; Dony Novaliendry; Titi Sriwahyuni; Syafrijon; Oktoria (Universitas Negeri Padang, 2026)
This study successfully designed and developed a blockchain-based crowdfunding system using Base, implementing secure authentication through wallet addresses as the primary user identity. The system supports key features such as campaign creation, donation, and fund withdrawal. Campaign creation allows users to set fundraising targets and deadlines, donations are recorded directly on the blockchain to ensure transparency, and fund withdrawals can only be performed by the campaign owner once specific conditions are met. The implementation of smart contracts played a vital role in ensuring that all transactions were transparent, secure, and accountable. Furthermore, the system effectively eliminated the need for intermediaries, as typically seen in conventional platforms, by replacing the role of fund custodians with smart contracts. As a result, it no longer required high administrative fees, instead relying on a fixed and significantly lower gas fee. This approach enhanced public trust, reduced operational costs, and strengthened accountability in the management of donations through a decentralized and tamper-resistant system.